2015
DOI: 10.1111/geoa.12085
|View full text |Cite
|
Sign up to set email alerts
|

The caribbean low‐level jet, the inter‐tropical convergence zone and precipitation patterns in the intra‐americas sea: a proposed dynamical mechanism

Abstract: circulation seems to be consistent during years when latitudinal center of mass is lower than normal, apparently reinforcing the jet, and presents weaker strength during years of high latitudinal center of mass. The proposed mechanism is explained in some detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
117
1
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(139 citation statements)
references
References 40 publications
(55 reference statements)
3
117
1
18
Order By: Relevance
“…It is known that in the summer months (JJA) during warm (cold) ENSO episodes the CLLJ is stronger (weaker) than normal (Amador, 2008) with a correlation of −0.53 (p value < 0.01). Hidalgo et al (2015) also noted that during stronger (weaker) CLLJ the ITCZ is located south (north) from the normal position, leading to a reduction (increase) in the total precipitation during boreal summer (JJA), thus, affecting the MSD. Therefore, the bottom line of this result is that the ENSO events modulate the intensity and magnitude of the MSD.…”
Section: General Features Of the Msdmentioning
confidence: 94%
See 1 more Smart Citation
“…It is known that in the summer months (JJA) during warm (cold) ENSO episodes the CLLJ is stronger (weaker) than normal (Amador, 2008) with a correlation of −0.53 (p value < 0.01). Hidalgo et al (2015) also noted that during stronger (weaker) CLLJ the ITCZ is located south (north) from the normal position, leading to a reduction (increase) in the total precipitation during boreal summer (JJA), thus, affecting the MSD. Therefore, the bottom line of this result is that the ENSO events modulate the intensity and magnitude of the MSD.…”
Section: General Features Of the Msdmentioning
confidence: 94%
“…Recently, Hidalgo et al (2015) also found that the latitudinal position of the precipitation centre of mass is correlated with the intensity of the CLLJ, i.e a weaker (stronger) jet is associated to the northward (southward) shift of the latitudinal precipitation centre of mass, resulting in rainfall above normal during JJA that might be also associated with variations of the MSD events.…”
mentioning
confidence: 94%
“…Several authors have pointed to the seasonal migration of the Intertropical Convergence Zone (ITCZ), deep convection, low-level moisture transport, cyclone activity, and mid-latitude air intrusions as being the main drivers of regional precipitation (Schulz et al, 1997;Amador et al, 2006;Durán-Quesada et al, 2010;among others). Studies on the effect of large-scale structures such as the ITCZ on regional precipitation are scarce (Hidalgo et al, 2015), and some important interactions, including links with the tropical Pacific, are not fully understood. The region is influenced by deep convection and highly active stratiform precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…13), se puede justificar este mínimo. La marcha hacia el norte de la ZCIT, genera alrededor de este mes ese máximo relativo de precipitación en esta zona (Magaña, Amador, & Medina, 1999;Shang-Ping et al, 2005;Amador et al, 2006;Quirós, 2015;Hidalgo et al, 2015). La distribución espacial superficial del oxígeno disuelto en el PTE está en relación con la variación espacial de los afloramientos del DTCR y del Golfo de Panamá, que tienen relación también, con en la marcha anual de la ZCIT.…”
Section: Discussionunclassified
“…La variación estacional del viento y la oscilación meridional de la Zona de Convergencia Intertropical (ZCIT) (e.g. Quirós, 2015;Hidalgo, Durán-Quesada, Amador, & Alfaro, 2015), modifican la dinámica del PTE (Kessler, 2006). varios trabajos se han escrito sobre el Domo Térmico de Costa Rica (DTCR) por su singular productividad (Wyrtki, 1964;Umatani, & Yamagata, 1991;Fiedler, 1992;Fiedler, 1994), entre otros.…”
unclassified